Shifts in developmental timing, and not increased levels of experience-dependent neuronal activity, promote barrel expansion in the primary somatosensory cortex of rats enucleated at birth. - Ingrid Fetter-Pruneda; Helga Geovannini-Acuña; Cecilia Santiago; Ana Sofía Ibarrarán-Viniegra; Eduardo Martínez-Martínez; Marcela Sandoval-Velasco; Laura Uribe-Figueroa; Patricia Padilla-Cortés; Gabriela Mercado-Célis; Gabriel Gutiérrez-Ospina (PLoS ONE, 2013)
Birth-enucleated rodents display enlarged representations of whiskers (i.e., barrels of the posteromedial subfield) in the primary somatosensory cortex. Although the historical view maintains that barrel expansion is due to incremental increases in neuronal activity along the trigeminal pathway during postnatal development, recent evidence obtained in experimental models of intramodal plasticity challenges this view. Here, we re-evaluate the role of experience-dependent neuronal activity on barrel expansion in birth-enucleated rats by combining various anatomical methods and sensory deprivation paradigms. We show that barrels in birth-enucleated rats were already enlarged by the end of the first week of life and had levels of metabolic activity comparable to those in control rats at different ages. Dewhiskering after the postnatal period of barrel formation did not prevent barrel expansion in adult, birth-enucleated rats. Further, dark rearing and enucleation after barrel formation did not lead to expanded barrels in adult brains. Because incremental increases of somatosensory experience did not promote barrel expansion in birth-enucleated rats, we explored whether shifts of the developmental timing could better explain barrel expansion during the first week of life. Accordingly, birth-enucleated rats show earlier formation of barrels, accelerated growth of somatosensory thalamocortical afferents, and an earlier H4 deacetylation. Interestingly, when H4 deacetylation was prevented with a histone deacetylases inhibitor (valproic acid), barrel specification timing returned to normal and barrel expansion did not occur. Thus, we provide evidence supporting that shifts in developmental timing modulated through epigenetic mechanisms, and not increased levels of experience dependent neuronal activity, promote barrel expansion in the primary somatosensory cortex of rats enucleated at birth.